Transcriptomes in rat sciatic nerves at different stages of experimental autoimmune neuritis determined by RNA sequencing - Xue, Y. (Clin Exp Immunol, 2019)
Guillain–Barré syndrome (GBS) is characterized by acute immune‐mediated peripheral neuropathy, which may result in rapidly progressive paralysis and fatal respiratory failure. As the underlying pathological mechanisms of GBS are unclear, we surveyed the transcriptome of rats with experimental autoimmune neuritis (EAN), a model of GBS. Briefly, sciatic nerves on both sides were collected from 8–10‐week‐old Lewis rats during early (10 days post‐induction), peak (19 days) and late neuritis (30 days). Total RNA was sequenced to identify differentially expressed genes. Compared to control rats without induced neuritis, 33 genes were differentially expressed in the early phase (14 up‐regulated and 19 down‐regulated), with an adjusted P‐value < 0·05 and |log(2) fold‐change| >1, as were 137 genes in the peak phase (126 up‐regulated and 11 down‐regulated) and 60 genes in the late phase (58 up‐regulated and two down‐regulated). Eleven of these genes were common to all stages, suggesting their crucial roles throughout the disease course. Analysis of protein–protein interactions revealed Fos, Ccl2, Itgax and C3 as node genes at different stages. Functional analysis of differentially expressed genes identified biological processes and pathways that are activated as neuritis progresses. This is the first genomewide gene expression study of peripheral nerves in experimental autoimmune neuritis model. Dynamic gene expression and significantly altered biological functions were detected in different phases of the disease, increasing our understanding of the molecular mechanisms underlying EAN and highlighting potential targets for its diagnosis and treatment.